Generation of two Duchenne muscular dystrophy patient-specific induced pluripotent stem cell lines DMD02 and DMD03 (MUNIi001-A and MUNIi003-A) - Jelinkova, Sarka; Markova, Lenka; Pesl, Martin; Valáškova, Iveta; Makaturová, Eva; Jurikova, Lenka; Vondracek, Petr; Lacampagne, Alain; Dvorak, Petr; Meli, Albano C; Rotrekl, Vladimir (Stem cell research, 2019)
Duchenne muscular dystrophy (DMD) affects 1:3500-5000 newborn boys and manifests with progressive skeletal muscle wasting, respiratory failure and eventual heart failure. Symptoms show different onset from patients' childhood to the second decade of age. We reprogrammed fibroblasts from two independent DMD patients with a complete loss of dystrophin expression, carrying deletions of exons 45-50 and 48-50. The resulting hiPSCs show expression of pluripotency markers (NANOG, OCT4, SSEA4), differentiation capacity into all three germ layers, normal karyotype, genetic identity to the originating parental fibroblasts and the patient-specific dystrophin mutation.
Keywords: Muscular Dystrophy, Duchenne; sekvenční delece; buněčné linie; Octamer Transcription Factor-3; dítě; Induced Pluripotent Stem Cells; Adolescent; buněčná diferenciace; lidé; indukované pluripotentní kmenové buňky; oktamerní transkripční faktor 3; Cell Line; Male; Duchennova muskulární dystrofie; Exons; Dystrophin; dystrofin; exony; Cell Differentiation; Child; mužské pohlaví; Sequence Deletion; mladiství; Humans